Answer:
(x-1)²+ (y-0.5)²=6.25
Step-by-step explanation:
<u>The standard form of equation of a circle is;</u>
(x-a)²+(y-b)²=r² where (a,b) are the center of the circle and r is the radius
<u>Finding the mid-point of the given points</u>
(-1,2) and (3,-1)⇒midpoint will be 1/2(x₁+x₂) , 1/2(y₁+y₂)
midpoint= {1/2(-1+3), 1/2(2+-1)}
midpoint=(1,0.5)
<u>Finding the radius r; the distance from the center to either of the given two points</u>
Apply the distance formula d=√ (x₂-x₁)² +(y₂-y₁)²
Taking (x₁,y₁) as (1,0.5) and (x₂,y₂) as (-1,2) then
d=√ (-1-1)² +(2-0.5)²
d= √ (-2)²+(1.5)²
d=√4+2.25⇒√6.25⇒2.5
r=2.5
<u>Equation of the circle</u>
(x-1)² + (y-0.5)²=2.5²
(x-1)²+ (y-0.5)²=6.25
Answer:
3,089.71
Step-by-step explanation:
divide 74,153 by 12 and by 2
Answer:
Angle B: 28 degrees
Side a: 27.6
Step-by-step explanation:
Angle B:
180-112-40=28
Side a:
sin 28/14 = sin 112/a
a = sin 112(14)/sin 28
a = 27.6
5 degrees. Since its a right triangle, one of the angles is a right angle meaning it measures 90 degrees and 90+85=175 degrees and because of the Triangle Sum Theorem, we know a triangle equals 180 degrees. So 180-175= 5 degrees.